A proof-of-concept, randomized controlled trial of DAR-0100A, a dopamine-1 receptor agonist, for cognitive enhancement in schizophrenia. (May 2016) - Girgis, Ragy R; Van Snellenberg, Jared X; Glass, Andrew; Kegeles, Lawrence S; Thompson, Judy L; Wall, Melanie; Cho, Raymond Y; Carter, Cameron S; Slifstein, Mark; Abi-Dargham, Anissa; Lieberman, Jeffrey A
Background: Evidence from preclinical and human studies indicates the presence of reduced dopamine-1 receptor (D1R) signaling in the cortex, where D1Rs predominate, in patients with schizophrenia (SCZ), which may contribute to their cognitive deficits. Furthermore, studies in nonhuman primates (NHP) have suggested that intermittent administration of low doses of D1R agonists produce long-lasting reversals in cognitive deficits. The purpose of this trial was to test whether a similar design, involving subacute intermittent administration of low doses of a full, selective agonist at D1Rs, DAR-0100A, would improve cognitive deficits in SCZ. Methods: We randomized 49 clinically stable individuals with SCZ to three weeks of intermittent treatment with 0.5 mg or 15 mg of DAR-0100A, or placebo (normal saline). Functional magnetic resonance imaging (fMRI) BOLD was used to evaluate the effects of drug administration on brain activity during a working memory (WM) task. Effects on cognition were also assessed using the MATRICS and the N-back task as primary endpoints. The CogState battery was used as a secondary endpoint. Results: There were no observed treatment effects on either the BOLD fMRI signal during WM tasks or the WM domains of the MATRICS. Moderate improvement was detected on the CogState battery and on the attention domain of the MATRICS. Conclusion: These results suggest that low doses of D1 agonists that do not result in measureable occupancy of the D1R do not reliably improve cognition in SCZ, unlike the observations in NHP. As this drug is limited by its pharmacokinetic profile, better D1R agonists that can achieve adequate levels of D1R occupancy are needed to test the efficacy of this mechanism for cognitive enhancement in SCZ.